1968
DOI: 10.1042/bj1060913
|View full text |Cite
|
Sign up to set email alerts
|

The sedimentation of rat skeletal-muscle ribosomes. Effect of hydrocortisone, insulin and diet

Abstract: 1. The influence of hydrocortisone, insulin and diet on the size distribution of ribosomes in a post-mitochondrial supernatant prepared from rat skeletal muscle was studied by sedimentation analysis with a linear 15-40% (w/v) sucrose gradient. 2. Within 4hr. after the injection of 5mg. of hydrocortisone to well-nourished rats, a decrease in the yield per g. of muscle and proportion of total RNA due to polyribosomes was observed. Similar results were obtained in rats given a protein-free diet for 3 days before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The rapid suppression of protein synthesis (i.e. 3 h; Table 1B) is in keeping with the suggestion that the acute response to these steroids is a decrease in the initiation of translation (Rannels & Jefferson, 1980) and is accompanied by a rapid (4h) decrease in the proportion of polyribosomes (Young et al, 1968;Bullock et al, 1972). Such initial responses are followed by an inhibition of transcription and consequent decreases in the muscle's RNA content.…”
Section: +6supporting
confidence: 78%
See 1 more Smart Citation
“…The rapid suppression of protein synthesis (i.e. 3 h; Table 1B) is in keeping with the suggestion that the acute response to these steroids is a decrease in the initiation of translation (Rannels & Jefferson, 1980) and is accompanied by a rapid (4h) decrease in the proportion of polyribosomes (Young et al, 1968;Bullock et al, 1972). Such initial responses are followed by an inhibition of transcription and consequent decreases in the muscle's RNA content.…”
Section: +6supporting
confidence: 78%
“…These and previous studies in vitro suggest a common and concerted mode of action of the glucocorticoids in arresting muscle growth. DNA synthesis (Goldberg & Goldspink, 1975), the net transfer of amino acids (Kostyo & Remond, 1966;Lewis & Goldspink, 1981) and the rates of protein synthesis (Tables 1 and 2; Young et al, 1968) and protein breakdown (Tables 1 and 2) are all significantly inhibited in skeletal muscle within 4 h of exposure to these steroid hormones.…”
Section: +6mentioning
confidence: 97%
“…3). Our results pow support those of Young et al (1968), who showed a decrease in the polyribosome content of ribosomes from young rats treated with cortisol.…”
Section: Discussionsupporting
confidence: 93%
“…Although there is no direct correlation between the protein-synthesizing activity of such preparations and declining rates of muscle growth with age (Section IV/I), changes in the rate of synthesizing muscle protein are usually accompanied by changes in the activity and state of aggregation of isolated ribosomes when the nutritional and hormonal status of animals is altered experimentally (cf . Breuer & Florini, 1965;Florini & Breuer, 1966;Wool et al, 1968;Young & Alexis, 1968;Young, Chen & Macdonald, 1968 ; Bullock et al, 1972).…”
Section: (C) Evidence That the Activity Of Ribosomes From Muscle Can mentioning
confidence: 99%